Advanced hybrid artificial pancreas system improves on unannounced meal response - In silico comparison to currently available system. (November 2021) - Garcia-Tirado, Jose; Lv, Dayu; Corbett, John P.; Colmegna, Patricio; Breton, Marc D.
Highlights: Advanced hybrid closed-loop control offers flexibility on announced/unannounced meals. Improved glycemic control over unannounced meals in comparison to a legacy system. Complete system integration of key elements for releasing the burden on diabetes care while guaranteeing optimal blood glucose control: hypoglycemia supervision and hyperglycemia mitigation systems and automatic bolus priming system in an adaptive Model Predictive Control framework. Abstract: Background and objective: Glycemic control, especially meal-related disturbance rejection, has proven to be a major challenge for people with type 1 diabetes. In this manuscript, we introduce a novel, personalized, advanced hybrid insulin infusion system (a.k.a. artificial pancreas) based on the Model Predictive Control (MPC) methodology to adjust insulin infusion while automatically rejecting uninformed meals. Methods: The proposed advanced hybrid closed-loop system relies on the integration of three key elements: (i) an adaptive personalized MPC control law that modulates the control strength depending on recent past control actions, glucose measurements, and its derivative, (ii) an automatic Bolus Priming System (BPS) that commands additional insulin injections safely upon the detection of enabling metabolic conditions (e.g., an unacknowledged meal), and (iii) a new hyperglycemia mitigation system to avoid prevailing hyperglycemia. The benefits of the proposed system are demonstrated through simulations and tests using the most up-to-date Type 1 UVA/Padova simulator as preclinical stage prior to in vivo clinical tests. We used a legacy algorithm (USS Virginia), currently used in clinical care, as a benchmark controller. Results: Overall, the proposed control strategy enhanced by an automatic BPS improves glycemic control when compared with an available system. When a large meal is not announced (80g CHO), the proposed controller outperformed the legacy controller in time-in-target-range TIR (postprandial and overnight) and time-in-tight-range TTR (overall, postprandial, and overnight). Conclusion: The integration of a novel BPS into an advanced control system allowed to automatically reject unannounced meals. Exhaustive simulation studies indicated the safety and feasibility of the proposed controller to be deployed in human clinical trials.